Predictable Results in Unpredictable Times : Sukses Setiap Saat - Covey, Stephen R., 424860; Whitman, Bob 483729; England, Breck 483730; Normah Sir 483731 (Batu Caves, Selangor : PTS PROFESSIONAL PUBLISHING SDN. BHD., 2010)
Johor Corporation (JCorp);